Analisis Penerimaan Pendapatan Asli Daerah (PAD) Ditinjau Dari Kontribusi PAD, Elastisitas PAD dan Kinerja Pajak Daerah Pada Pemerintah Kota Sibolga - Deliana, Deliana; Jonni Parulian, Riatno; Hidayah Napitupulu, Ilham (DINASTI RESEARCH, 2024)
This study aims to analyze the contribution of local revenue, the elasticity of local revenue and the performance of local taxes in the Sibolga City government. Local Own Revenue is the right of the local government which is recognized as an increase in the value of net assets obtained from local taxes, local levies, the results of the management of separated local assets and other legitimate local revenue. This research was tested on the sibolga city local government in 2018-2022. The data analysis technique used in this research is descriptive and quantitative analysis. The results of the analysis show that the contribution of local revenue tends to be unfavorable, the elasticity of local revenue tends to be elastic to gross regional domestic product and the performance of local taxes tends to be very effective.